2005
DOI: 10.1103/physrevlett.94.184505
|View full text |Cite
|
Sign up to set email alerts
|

Drop Splashing on a Dry Smooth Surface

Abstract: The corona splash due to the impact of a liquid drop on a smooth dry substrate is investigated with high speed photography. A striking phenomenon is observed: splashing can be completely suppressed by decreasing the pressure of the surrounding gas. The threshold pressure where a splash first occurs is measured as a function of the impact velocity and found to scale with the molecular weight of the gas and the viscosity of the liquid. Both experimental scaling relations support a model in which compressible eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
608
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 640 publications
(643 citation statements)
references
References 17 publications
33
608
2
Order By: Relevance
“…The experiments of Stow and Hadfield (1981) as well as those of Range and Feuillebois (1998) have shown that rougher surfaces exhibit a lower value of K, and therefore more splashing [5,6]. Xu (2005) found that decreasing the ambient gas pressure raises the splashing threshold, proving that the liquid's interaction with the ambient gas is essential for splashing to occur.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The experiments of Stow and Hadfield (1981) as well as those of Range and Feuillebois (1998) have shown that rougher surfaces exhibit a lower value of K, and therefore more splashing [5,6]. Xu (2005) found that decreasing the ambient gas pressure raises the splashing threshold, proving that the liquid's interaction with the ambient gas is essential for splashing to occur.…”
Section: Introductionmentioning
confidence: 87%
“…A rich body of literature already exists considering perpendicular drop impacts, with a droplet falling from above onto a flat surface [1][2][3][4][5][6][7][8]. These studies have revealed the underlying mechanics and possible outcomes of droplet splashing and are industrially relevant to processes such as spray coating, spray cooling and inkjet printing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the substrate on the spreading and splashing has been studied in [126,[137][138][139][140][141]. Recent research by Nagel's and Brenner's groups has identified that the compressibility of the gas, here air surrounding the droplet [142,143] affects the splashing. For typical BPA situations, their results agree with the criterion of equation (11).…”
Section: An Example Of Current Capabilities Of Computational Fluid Dymentioning
confidence: 99%
“…As we can see in figure 6 (b) and (e), the turbulent mixing is slightly higher for figure 6 (e); and the velocity at the bottom of the tunnel is also higher in both cases (T D ={5s and 10s}) for H=10m. Water isovolume in the simulation can be seen in figure 7, where we can see water splashes closer to the door as the gate opens; it is due to pressure difference between tank and tunnel [29] and variable density model which is mentioned in section 3.1. Figure 8 shows the flow rate through the gate.…”
mentioning
confidence: 95%